2020
DOI: 10.1088/1361-648x/abbcfa
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of gas molecules of CH4, CO and H2O on the vanadium dioxide monolayer: computational method and model

Abstract: Inspired by the recent use of two-dimensional nanomaterials as gas sensors, we used density functional theory calculations to study the adsorption of gas molecules (CH4, CO and H2O) on sandwich vanadium dioxide tablets. The results showed that of all these gases, only the CH4 gas molecule was the electron acceptor with significant charge transfer on the VO2 sheet. The adsorption energies of CH4, CO and H2O are −229.5 meV, −239.1 meV and −388.3 meV, respectively. We have also compared the adsorption energy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Since its first successful fabrication, black phosphorene (αphosphorene) has garnered significant interest for a range of applications (see the reviews and references therein) [1][2][3][4]. Phosphorene's remarkable electrical and magnetic properties [5][6][7][8][9] make it a promising candidate for use in electronics, spintronics, and gas sensors [6,8,[10][11][12][13][14]. However, the primary challenge for practical applications of 2D black phosphorus is its poor ambient stability, necessitating encapsulation by inert 2D materials such as h-BN [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Since its first successful fabrication, black phosphorene (αphosphorene) has garnered significant interest for a range of applications (see the reviews and references therein) [1][2][3][4]. Phosphorene's remarkable electrical and magnetic properties [5][6][7][8][9] make it a promising candidate for use in electronics, spintronics, and gas sensors [6,8,[10][11][12][13][14]. However, the primary challenge for practical applications of 2D black phosphorus is its poor ambient stability, necessitating encapsulation by inert 2D materials such as h-BN [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Long Lin et al showed through theoretical studies that co-doping Mn and Co atoms in the wideband gap semiconductor SnO 2 stabilizes the ferromagnetic state [15,16]. Theoretical studies also show that dilute magnetic systems could be used for gas sensing applications [17][18][19].…”
Section: Introductionmentioning
confidence: 99%